Participatory Communication for Sustainable Rural Livelihoods : Insights from Matatiele Local Municipality - Moroesi Lebenya; Betty Claire Mubangizi; Oluwaseun Temitope Ojogiwa (Institutiones Administrationis, 2024)
Traditional top-down approaches exclude communities from participating in policy design and decision-making, while existing communication models are inadequate in addressing communication and service delivery challenges in rural municipalities. And Matatiele Local Municipality (MLM) is no exception. This study is focusing on Matatiele Local Municipality’s use of participatory communication (PC) processes in line with democratic principles and their impact on service delivery. It explores the communication practices, the nexus between good governance and participatory communication and identifies approaches towards participatory communication in rural Matatiele. From an interpretivism paradigm, the study employed a qualitative research method that permit a focused examination of nineteen purposively selected participants. Data retrieved from the semi-structured interview and from secondary sources was analysed thematically and narratively. Findings indicate that participatory communication is not uniformly applied across all areas within MLM jurisdiction. Infrastructure deficits, service delivery challenges and issues related to decentralisation are also identified. The study concludes that traditional authorities play a significant yet overlooked role in democratic development at the local level. Recommendations include an emphasis on the reassessment of the role citizens play in the decision-making process to enhance their meaningful involvement and empowerment in the governance process beyond participation by consultation. Therefore, participatory communication practices beyond establishing clear feedback mechanisms, enhancing responsiveness to community concerns, and improving citizens’ influence on final decisions can promote mutual understanding and cocreation of content that could enhance citizens’ livelihoods.